THE ASSOCIATION OF PERFORMANCE, AWARDS, OWNERSHIP, AND MEDIA WITH THE ENVIRONMENTAL DISCLOSURE - Adita Mutiara Annisa; Husnah Nur Laela Ermaya (JRAK, 2022)
This research aims at analyzing and empirically testing the effect of environmental performance, environmental awards, institutional ownership, and media coverage at 32 non-financial companies listed on the Indonesia Stock Exchange and PROPER for the period 2018 – 2020 with 96 data and analyzed using multiple regression. The result of the statistical tests has proven that institutional ownership has a significantly negative effect on environmental disclosure. Meanwhile, environmental performance, environmental awards, and media coverage do not affect environmental disclosure.